2020
DOI: 10.1186/s12902-020-00631-3
|View full text |Cite
|
Sign up to set email alerts
|

Obesity epidemic in urban Tanzania: a public health calamity in an already overwhelmed and fragmented health system

Abstract: Background Worldwide, the epidemiological and demographic transitions have resulted in nutrition shift characterized by an increased consumption of high energy fast food products. In just over 3 decades, overweight and obesity rates have nearly tripled to currently affecting over a third of the global population. Notwithstanding the ever present under-nutrition burden, sub Saharan Africa (SSA) is witnessing a drastic escalation of overweight and obesity. We aimed to explore the prevalence and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 63 publications
(110 reference statements)
5
15
1
Order By: Relevance
“…Reported by about 3% of participants in this study, tobacco use was the least prevalent risk factor in this setting. Similar tobacco use rates have been reported in Dar es Salaam city by a couple of previous community-based studies, 32 , 33 however, as per the WHO statistics of 2017 at least 14% of Tanzanian adults were current tobacco users. 34 Variable rates of tobacco use ranging from 2.9% in Nigeria to 49.9% in Bangladesh are reported by studies conducted in different communities.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Reported by about 3% of participants in this study, tobacco use was the least prevalent risk factor in this setting. Similar tobacco use rates have been reported in Dar es Salaam city by a couple of previous community-based studies, 32 , 33 however, as per the WHO statistics of 2017 at least 14% of Tanzanian adults were current tobacco users. 34 Variable rates of tobacco use ranging from 2.9% in Nigeria to 49.9% in Bangladesh are reported by studies conducted in different communities.…”
Section: Discussionsupporting
confidence: 84%
“…54 With the rapidly rising rates of overweight, hypertension and diabetes in Tanzania, it is increasingly becoming evident that the soaring rates of consumption of highly processed foods together with low levels of physical activity are playing a dominant role in the NCD epidemic. 33 , 55 , 56 Nonetheless, despite the wide variability in the rates of unhealthy eating (41.9–99.7%) and low physical activity (14.5–86.4%) from studies worldwide, the message is clear that both risks are increasing at a staggering rate. 12 , 15 , 23–28 , 35–46 , 49–51 , 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…The percentage of prepared food sources that served healthy food options were quite similar across the two cities. Food retail outlets' HFAS ranged from 0 to 11 with a median of 2 (1,5). The HFAS in Nairobi-based retail outlets were significantly higher than in Kisumu-based outlets [a median of 4 (2, 7) versus a median of 1 (1, 2), p-value < 0.0001].…”
Section: Availability Of Healthy and Unhealthy Foodsmentioning
confidence: 96%
“…Countries in the East African region are undergoing a nutrition transition with increasing prevalence of overweight and obesity among different population groups [ 1 , 2 , 3 , 4 , 5 ]. The most recent nationally-representative demographic health survey conducted in Kenya in 2014 showed that 23% of women of reproductive age were overweight while 10% were obese [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Questionnaires were used as the data collection tool. BMI, according to the World Health Organization standard measurements, was assessed with scale and measure tape [23].…”
Section: Study Techniquementioning
confidence: 99%